THE SIGNIFICANCE OF MACROECONOMIC AND FINANCIAL MARKET VARIABLES FOR FDI INFLOW IN ASIAN DEVELOPING COUNTRIES - Zada, Lal; Kashmiri, Rameez; Wadood, Fazli (The journal of contemporary issues in business and government, 2021)
This paper weighs up the effect of macroeconomic stability and financial development of host country in increasing its attractiveness for investors abroad. The significance of market size, level of development, openness and efficiency of stock market for inward Foreign Direct Investment (FDI) was also investigated. Yearly panel data for 7 countries from 1990 to 2015, covering 26 years were employed. The result shows that Gross Domestic Product (GDP) and Sound macroeconomic discipline proved significant for inward FDI. Furthermore, small percentage of inflation and exchange rate fluctuations and openness of a country were also positively significant. 1Stock market and 2financial development of a country except for private credit by bank positively strongly affect inward FDI.